Rola "motywów"i "zasług" w procedurze prawnej uzyskania tytułu arystokratycznego na Śląsku w nowej polityce Habsburgów po 1629 r. = The role of motives and merits in the legal procedure of gaining the aristocratic title in Silesia in the new policy of the Habsburgs after 1629 - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to obtain the title of a baron, count or duke, the applicant called the supplicant was obliged to present his request and proper, "enough" justification for the application. The justification usually contained the detailed genealogical lineage but, above all, merits - both of the family and one`s own.
Keywords: Śląsk - historia - 17 w.; Habsburgowie - historia - 17 w.; arystokracja